Pengaruh Rekrutmen, Seleksi, Dan Penempatan Karyawan Terhadap Kinerja Karyawan Pada PT Pos Indonesia Cabang Utama Semarang - Guruh Mulia Widayat; Wahyu Rizqy Amalinda; Teguh Ariefiantoro (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study aims to examine and analyze the effect of recruitment, selection, and placement of employees on the performance of employees of PT Pos Indonesia Main Branch Semarang. The research method used in this study uses quantitative methods. This research was conducted on 114 employees from various levels and departments at PT Pos Indonesia Main Branch Semarang. The data collection technique uses the questionnaire method which is then processed using the SPSS program. While the data testing techniques used in this study include validity test, reliability test with Alpha Cronhbach, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, and the coefficient of determination. The results of the analysis show that recruitment has no significant and negative effect on employee performance, selection has a positive and significant effect on employee performance, placement has no significant and negative effect on employee performance.